Numerical mathematics - Open University ([United Kingdom] : Open University, 1976)
Contains the foundations of matrix analysis, principles of numerical mathematics include direct methods for the solution of linear systems.
Convert into VHS 1/2 in. and DVD
Filem AS 122.O6 M201 filem 7
Bahan rosak (Lupus)
Keywords: Numerical analysis; Mathematics